PENGEMBANGAN PIRANTI HIBRID TERMOELEKTRIK – SEL SURYA SEBAGAI PEMBANGKIT LISTRIK RUMAH TANGGA - Ubaidillah Ubaidillah; Suyitno Suyitno; Wibawa Endra Juwana (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
The potential of waste heat from the sun is still not optimally utilized. Tool-based energy harvester optimized solar cells that are stored on the photons of light energy from the sun. This research aims to design and develop prototypes of alternative power scale household exploit the potential of photons (solar cells) and heat (thermoelectric cells) of solar radiation. The design process through standard mechanical design principles followed by the fabrication and assembly of prototypes. The solar panels are fitted with a solar tracker with sun position tracking strategy where data is entered into the position of the sun as a reference microcontroller motion solar cells. Tues thermoelectric apart from solar panels installed as the cold side equipped with air-water cooling. Testing the performance of solar cells and thermoelectric done separately for ease of measurement defined variables such as current, voltage and temperature. The equipment used for the measurement of variables - variables include multimeter, thermo-reader and pyranometer. The experimental results of solar panels on July 10, 2012 shows average power output - average of 25.75 W 10% higher than the panel passive (static). Testing TEC1-12 710 individual cells has been done to study the early determination of the number of cells that will be used on the TE module. By using 32 cells in series strung TE module has been tested in the field but has not shown the expected results.